The impact of sociodemographic characteristics on oral health behaviors of dental graduates - Arheiam, Dr.Arheiam; A Alobeidi, Dr.Badr; A Gaber, Dr.Amal; A Musrat, Dr.Ahmed; Garoush, Dr.Sufyan; A Benali, Dr. Nada; S Saad, Dr.Suleiman (Libyan Journal of Dentistry, 2020)
Background: To assess and compare oral health behaviors (OHB) of final year dental students in private and state-run dental schools in Benghazi city, Libya. Methods: Students from private and state-run dental schools were invited to participate in this cross-sectional study. A self-administered questionnaire including closed ended questions regarding socio-demographics and OHBs was used. The main OHBs explored were teeth brushing, the usage of fluoridated toothpaste, dental flossing, sugar consumption, dental visiting and smoking habit. Binary logistic regression models were utilized to explore associations between OHBs and socio-demographic variables Results: Out of 240 students invited, only 199 completed questionnaires were analyzed (effective response rate was 83%). The majority of the students were females (80%) who brushed their teeth daily (90.5%) and used fluoridated toothpaste (80.2%) while 30.2 % of them used dental floss and only 7% were smokers. Females were more likely to use fluoridated toothpaste (OR = 2.67, 95% CI = 1.21 – 5.97) and visit a dentist (OR = 2.31, 95% CI = 1.21 – 4.42) compared to males, and students in the private dental school consumed more sugary-snacks per day (OR = 3.2, 95% CI = 1.52 – 6.75) than those who studied in state schools. Conclusion: Socio-demographic variables such as gender and type of school were associated to certain oral health behaviors of dental students.